PERSEPSI SISWA TERHADAP PEMBELAJARAN SENI BUDAYA (SENI MUSIK) KELAS VII DI SMP NEGERI 11 PADANG - Ayulasti, Armila; Syeilendra, Syeilendra (SENDRATASIK UNP, 2019)
Abstract This article aims to find out and describe students' perceptions of cultural arts learning (Music Art) at SMP Negeri 11 Padang. This type of research was quantitative which can be interpreted as a research method based on positivism philosophy. The main instrument in this study was a questionnaire. Techniques of data collection were done by making statements, distributing questionnaires to students, collecting questionnaires that have been filled out, checking and processing data. The result shows that students' perceptions of cultural arts learning (Music Art), especially in unisono singing material, are in good category which can be seen from four questionnaire indicators namely the first is 88% of sonority which is categorized as excellent, the second is 83.9% of homogeneity which is categorized as excellent, and the third is 82.5% of ambitus is also categorized as excellent, and the last one is 77,5 % of Timbre which is categorized as a good one. Keywords: Students’ Perception, Cultural Arts (Music Art)